Allergic rhinitis control: contemporary approaches to evaluation - D. S. Tyufilin; I. A. Deev; O. S. Kobyakova; E. S. Kulikov; N. A. Tabakaev; D. A. Vinokurova; N. A. Kirillova (Бюллетень сибирской медицины, 2019)
Objectives. Allergic rhinitis (AR) is highly prevalent all around the world. It adversely affects the quality of life of patients and leads to the development of bronchial asthma, which determines its high socioeconomic burden. International and Russian authorities establish control of the disease as a primary efficacy end point of allergic rhinitis treatment. Nevertheless, there is no international, standardized, validated tool to assess control of allergic rhinitis. In this regard, this review aims to analyze research on the development of such tools and to provide their comparative analysis. Review methods. Using PubMed, Web of science and Russian Citation Index database, we searched from 1991 to 2019 with logical combinations of the following key words: “allergic rhinitis control”, “AR control”, “AR questionnaire”. A total of 96 publications were included in the study. Results. All studies were arranged in chronological order and their main results were described. Questionnaires on the quality of life, tools offered by the clinical guidelines, visual analogue scales, and specialized questionnaires for measuring the control of allergic rhinitis were considered separately. The advantages and disadvantages of these instruments are described. Conclusion. The evidence based on the quality of the tool to support the use of specialized questionnaires was shown. Many disease control scales have been validated, but have some practical disadvantages asprimary efficacy criteria in clinical practice.